Dimensi Teatrikal Tradisi Man Belo Masyarakat Lingga Perspektif Theatre of Cruelty Antonin Artaud - Nika Saputri; Tafsir Hudha (Institut Seni Indonesia Yogyakarta, 2026)
The Theatrical Dimensions of the Man Belo Tradition in the Lingga Community: An Antonin Artaud's Theatre of Cruelty Perspective.This study aims to reveal the problems related to the Man Belo tradition among women in Lingga Village. Man Belo is a custom practiced by women in Lingga Village since ancient times and is still practiced today. This study uses Antonin Artaud's Theatre of Cruelty perspective to read the intensity of the body, sensory experience, and theatrical dimension in the man belo tradition of the Lingga community. This study uses Antonin Artaud's theory of the Theatre of Cruelty which rejects the dominance of text and dialogue, then emphasizes the body, movement, sound and sensory shock to shake the audience. This study uses a qualitative approach with a performance ethnography method to understand the performative and theatrical dimensions in the man belo tradition of the Lingga community. The results show that the man belo tradition has performative and theatrical dimensions that emerge through body gestures, sensory experiences, non-verbal communication, and collective social rituals of Lingga women.Keywords: Man Belo, Theatre of Cruelty, Performative and Theatrical Dimensions